Think Pair Share Model for Improving Mathematics Learning Outcomes: Model Think Pair Share untuk Meningkatkan Hasil Belajar Matematika - Safitri, Juliana; Avana, Nurlev; Guswita, Reni (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Mathematics is a fundamental subject that supports the development of logical reasoning and problem-solving skills, yet it often poses difficulties for elementary students, resulting in low motivation and learning outcomes. Specific Background: Observations at grade VI of SDN 91/VI Rantau Panjang revealed that traditional teaching methods led to low participation, lack of collaboration, and 75% of students scoring below the minimum mastery criteria. Knowledge Gap: While previous studies confirm the effectiveness of Think Pair Share (TPS), limited evidence exists on its adaptation to the unique characteristics of grade VI learners in rural primary schools. Aims: This study aimed to improve student learning processes and outcomes in mathematics through the implementation of a modified TPS cooperative learning model. Results: Conducted as classroom action research in two cycles, the study showed significant improvements: teacher performance increased from 80% to 100%, student participation rose from 75% to 93.75%, and learning mastery improved from 75% to 93.75%. Novelty: The research introduced contextual modifications to the TPS model, such as flexible grouping, adjusted discussion time, and task variations aligned with the curriculum, which enhanced student engagement and comprehension. Implications: The findings demonstrate that TPS not only improves mathematical achievement but also fosters collaborative learning environments, offering a scalable strategy for broader application in primary education. Highlights: TPS increased participation and mastery in mathematics learning. Teacher performance and student collaboration improved significantly. Modified TPS provided contextual strategies for primary education. Keywords: Mathematics Learning, Cooperative Learning, Think Pair Share, Student Engagement, Learning Outcomes